2019
DOI: 10.1007/s41064-019-00076-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Assessment of Agricultural Crops Using Multi-temporal Dual-Polarimetric TerraSAR-X Data

Abstract: The biomass of three agricultural crops, winter wheat (Triticum aestivum L.), barley (Hordeum vulgare L.), and canola (Brassica napus L.), was studied using multi-temporal dual-polarimetric TerraSAR-X data. The radar backscattering coefficient sigma nought of the two polarization channels HH and VV was extracted from the satellite images. Subsequently, combinations of HH and VV polarizations were calculated (e.g. HH/VV, HH + VV, HH × VV) to establish relationships between SAR data and the fresh and dry biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In addition, we computed mathematical band combinations (MBC) of both polarization in terms of addition (VH+VV), subtraction (VH-VV, VV-VH), ratio (VH/VV, VV/VH), and multiplication (VH * VV). These MBCs were reported to counteract radiometric instability and vegetation moisture variations introduced by using original polarization (e.g., Omar et al, 2017;Ahmadian et al, 2019) and hence are likely able to improve the performance of our empirical model. The definition of Kennaugh's matrix and its elements for dual-pol S1 data was used based on the calculation by Schmitt et al (2015) and Ullmann et al (2017).…”
Section: Sar-based Parametersmentioning
confidence: 90%
“…In addition, we computed mathematical band combinations (MBC) of both polarization in terms of addition (VH+VV), subtraction (VH-VV, VV-VH), ratio (VH/VV, VV/VH), and multiplication (VH * VV). These MBCs were reported to counteract radiometric instability and vegetation moisture variations introduced by using original polarization (e.g., Omar et al, 2017;Ahmadian et al, 2019) and hence are likely able to improve the performance of our empirical model. The definition of Kennaugh's matrix and its elements for dual-pol S1 data was used based on the calculation by Schmitt et al (2015) and Ullmann et al (2017).…”
Section: Sar-based Parametersmentioning
confidence: 90%
“…Manual production estimation is tedious and can produce significant errors. In exploring more scientific and precise methods, scientists have begun to use crop growth models and machine algorithms to study the crop growth process and yield ( Liaqat et al, 2017 ; Mehta et al, 2018 ; Ahmadian et al, 2019 ; Li et al, 2021 ). At present, many crop growth models have been applied, such as APSIM, DSSAT, WOFOST, etc., which can accurately simulate crop growth stage by changing the parameter Settings of crop growth stage ( Rosa, Souza & Tsukahara, 2020 ; Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies examining the assimilation of aboveground biomass are rare and often use field measurements instead of estimates based on remote sensing data [17]- [19]. However, different authors have shown the potential of SAR data to estimate above ground biomass components of different crops using simple regressions or machine learning approaches [20]- [24]. Moreover, authors also showed that the simultaneous assimilation of optical and SAR data often allowed a better optimization of agrometeorological models [19], [25], [26].…”
Section: Introductionmentioning
confidence: 99%